Simultaneous Presentation of Multiple Myeloma and Lung Cancer: Case Report and Gene Bioinformatics Analysis - Xiao, Ping-Ping; Luo, Bing-Qing; Fan, Wei; Chen, Xu-Yan; Dong, Zhi-Gao; Huang, Jin-Mei; Zhang, Yi; Chen, Yong-Quan (Frontiers in Oncology, 2022)
Generally, patients with multiple cancer types develop different cancers sequentially. Few cases of simultaneous occurrences of multiple myeloma and lung cancer have been reported in the literature. Here, we report two cases of the simultaneous occurrence of multiple myeloma and lung cancer presenting as pain. Haematology, biochemistry, bone marrow and lung occupation histopathological examination confirmed the diagnosis of multiple myeloma and lung cancer.We provided suitable interventions for two patients. Patients were still currently undergoing therapy with follow-up examinations. We first performed a bioinformatics analysis to determine the genes and pathways that these two types of cancer may share. Fortunately, we discovered the hub gene MECR, which was overexpression between the two tumors, Survival analysis demonstrated that high expression of MECR with poor overall survival. Signaling pathway analysis demonstrated possible transduction pathways.The clinical cases combined with bioinformatic analysis maybe help reveal the deeper mechanisms between two tumors.